Предмет: Алгебра,
автор: sennikova
УПРОСТИТЬ ((2-2sin^2x)/(1-cos2x))+(tgx*ctgx)
Ответы
Автор ответа:
0
((2-2sin^2x)/(1-cos2x))+(tgx*ctgx)=(2*(1-sin^2x)/(1-cos^2x+sin^2x))+1=
=(2*cos^2x/(2*sin^2x))+1=ctg^2x+1=1/(sin^2x)
=(2*cos^2x/(2*sin^2x))+1=ctg^2x+1=1/(sin^2x)
Автор ответа:
0
исправил... ошибочка с 2 была
Похожие вопросы
Предмет: Русский язык,
автор: luizaalizanova959
Предмет: Физика,
автор: saintso222
Предмет: Алгебра,
автор: moscowbut10
Предмет: Информатика,
автор: ilyaatata
Предмет: Математика,
автор: KrameRR